Corrosion Inhibition Of Mild Steel In 1 M Hydrochloric Acid Solution By Cymbopogon Citratus Leaves Extract - Hamzah, Ali Hassan (Universiti Sains Malaysia, 2017)
The inhibitive effect of naturally available Cymbopogon citratus leaves extract toward the corrosion of mild steel in 1M hydrochloric acid (HCl) solution has been investigated by weight loss measurement. The corrosion rate of mild steel was decreased in the presence of C. citratus extract. The corrosion inhibition efficiency increases on the increasing C. citratus extract concentration until 2 g/L to attain about 92% at 30°C. The effects of temperature, acid concentration and immersion time on the corrosion rate of mild steel in HCl solution either in the absence or presence of C. citratus extract were also studied. Fourier Transform Infrared (FT-IR) spectroscopy analysis was also carried out to establish the corrosion inhibitive properties of this plant extract in HCl solution. The results showed that the adsorption of the extract on the mild steel surface obeys Langmuir isotherm and physical adsorption mechanism.